Response to therapy with tafamidis 61 mg in patients with cardiac transthyretin amyloidosis: real-world experience since approval - Siepen, Fabian aus dem; Meissner, Christopher; Hofmann, Eva Catarina Maria; Hein, Selina; Nagel, Christian; Hegenbart, Ute; Schönland, Stefan; André, Florian; Frey, Norbert; Kristen, Arnt (Amyloid, 2024)
Transthyretin amyloid cardiomyopathy (ATTR-CM) is a progressive disease that causes heart failure due to amyloid fibril deposition. Tafamidis was approved as the first causal treatment in 2020. We here report on real-world data in patients treated with tafamidis for at least 12 months according to the recently defined European Society for Cardiology (ESC) consensus criteria for disease progression. Three hundred and eight wildtype and 31 hereditary ATTR-CM patients were prospectively enrolled after first diagnosis of ATTR-CM and initiation of tafamidis 61 mg once daily treatment. After 12 months, significant deterioration in Karnofsky Index, estimated glomerular filtration rate (eGFR), N-terminal brain natriuretic peptide (NT-proBNP), septum thickness and left ventricular ejection fraction (LVEF) could be observed, significant disease progression was only detected in 25 patients (9%) using ESC consensus criteria. Mean survival time was 37 months with no differences between responders and non-responders. NT-proBNP was the only independent predictor for poor therapy response (p = .008). The majority of patients showed no significant disease progression according to the ESC consensus criteria after 12 months of therapy with tafamidis. However, at 12 months, treatment response based on the ESC consensus criteria was not associated with improved survival. Moreover, higher levels of NT-proBNP at diagnosis of ATTR-CM appears to predict poorer treatment response, confirming that timely initiation of therapy is advantageous.
Gesehen am 09.12.2024